Chlorophobic iron hydrogen phosphite as OER-active electrocatalyst in anion exchange membrane (sea)water electrolysis - Das, Chandni; Sinha, Nibedita; Nair, Aathira; Pal, Santanu; Joshi, Kavita; Roy, Poulomi (Small, 2025)
Seawater electrolysis is recognized as a promising technology to cater to the worldwide drive for sustainable hydrogen production; however, its practical viability is often hindered by the inevitable anode corrosion arising from the electrode side reactions owing to the presence of high chloride content which eventually degrade the electrode performance eventually. Herein, the design of unprecedented ammonium iron hydrogen phosphite (FeHPhi) along with a trace amount of Cu, is reported as the unique and much desired electrode material for seawater electrolysis due to its special chloride repellant nature along with great electrocatalytic activity toward water oxidation. The [HPO3](2-) oxoanion as Lewis base in the structure effectively restricts chloride ions, while the Fe center acts as Lewis acid offering an active site for water oxidation, also well-supported theoretically. Leveraging this frustrated Lewis pair combination, the electrocatalyst achieves a high current density of 500 mA cm(-2) at 344 mV overpotential in alkaline real seawater with impressive robustness to sustain for 200 h when operated under chlorine evolution reaction dominating region (>2 V). The electrocatalyst also demonstrates superior performance in anion exchange membrane freshwater and seawater electrolysis, demonstrating its potential applicability.
Keywords: AEM electrolyzer; chloride repellant; electrocatalyst; hydrogen production; seawater oxidation